Pengaruh Implementasi Aplikasi Sistem Keuangan Desa, Sistem Pengendalian Internal Pemerintah Desa dan Transparansi terhadap Kualitas Laporan Keuangan Desa pada Pemerintahan Desa di Kecamatan Klari Kabupaten Karawang - Nuroniyah, Rani Esa; Yanti; Lasmini, Lilis (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to examine the effect of village financial system application implementation, village government internal control system and transparency on the quality of village financial statements in village government in Klari District, Karawang Regency. The population in this study is 13 Village Governments in Klari District, Karwang Regency. The sampling technique used in this study was a saturated sampling technique, with samples taken as many as 100 respondents. The subject of this study was the village government apparatus in Klari sub-district. Data collection using questionnaires, To analyze the relationship between variables using PLS with SmartPLS 3.0 software. The results showed that the implementation of village financial system applications and the village government's internal control system had a positive and significant effect on the quality of village financial statements. Meanwhile, transparency does not have a positive and significant effect on the quality of village financial reports. Keywords: Village Financial System Implementation, Village Government Internal Control System, Transparency, Quality of Village Financial Statements